Konsep Tetandingan Jaje Sarad Pulagembal Sebagai Seni Lukis - Adi Udyana, I Made; Muka, I Ketut; Ruta, Made (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2022)
Jaje Sarad Pulagembal is one of the complementary facilities for the ceremony that attracts the attention of many people, not only the Balinese Hindu community, but also the wider community. In addition to being quite large, it also looks beautiful because it is arranged very artistically. Jaje Sarad Pulagembal is usually displayed in the courtyard of the temple, but not many people know what the purpose and meaning of Jaje Sarad is. Jaje Sarad is usually made during the implementation of the Madyaning Utama piodalan and above, namely the piodalan that uses bebangkit and the ceremony that uses Pulagembal. The method of creation is a systematic way of creating works of art. The stages of creating a work of art that outlines the design of the process of creating a work of art in accordance with the stages of creation from inspiration (ideas), design, to embodiment. How to realize an idea into a painting, of course, is not necessarily done without preparation. Preparation in this process can be divided into 5 stages of creation: (1) preparation, (2) elaboration, (3) synthesis, (4) concept realization, (5) completion or evaluation. In the title chosen, namely